SARS-CoV-2 spike promotes inflammation and apoptosis through autophagy by ROS-suppressed PI3K/AKT/mTOR signaling - Li, Fei; Li, Jingyao; Wang, Pei-Hui; Yang, Nanyan; Huang, Junyu; Ou, Jinxin; Xu, Ting; Zhao, Xin; Liu, Taoshu; Huang, Xueying; Wang, Qinghuan; Li, Miao; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection-induced inflammatory responses are largely responsible for the death of novel coronavirus disease 2019 (COVID-19) patients. However, the mechanism by which SARS-CoV-2 triggers inflammatory responses remains unclear. Here, we aimed to explore the regulatory role of SARS-CoV-2 spike protein in infected cells and attempted to elucidate the molecular mechanism of SARS-CoV-2-induced inflammation. SARS-CoV-2 spike pseudovirions (SCV-2-S) were generated using the spike-expressing virus packaging system. Western blot, mCherry-GFP-LC3 labeling, immunofluorescence, and RNA-seq were performed to examine the regulatory mechanism of SCV-2-S in autophagic response. The effects of SCV-2-S on apoptosis were evaluated by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), Western blot, and flow cytometry analysis. Enzyme-linked immunosorbent assay (ELISA) was carried out to examine the mechanism of SCV-2-S in inflammatory responses. Angiotensin-converting enzyme 2 (ACE2)-mediated SCV-2-S infection induced autophagy and apoptosis in human bronchial epithelial and microvascular endothelial cells. Mechanistically, SCV-2-S inhibited the PI3K/AKT/mTOR pathway by upregulating intracellular reactive oxygen species (ROS) levels, thus promoting the autophagic response. Ultimately, SCV-2-S-induced autophagy triggered inflammatory responses and apoptosis in infected cells. These findings not only improve our understanding of the mechanism underlying SARS-CoV-2 infection-induced pathogenic inflammation but also have important implications for developing anti-inflammatory therapies, such as ROS and autophagy inhibitors, for COVID-19 patients. •SARS-CoV-2 spike triggers autophagy and apoptosis in ACE2-expressing cells.•SARS-CoV-2 spike induces autophagy through ROS-suppressed PI3K/AKT/mTOR pathway.•SARS-CoV-2 spike-induced autophagy promotes inflammatory responses and apoptosis.